Assessing the effectiveness of selected European innovation systems - Edyta Dworak (Comparative Economic Research. Central and Eastern Europe, 2022)
The growing importance of innovation in the modern economy has revived the interest of economic sciences in studies on the mechanisms that govern innovation and its impact on economic development. This growth of interest induced the concept of the national system of innovation (NSI), which occupies an important place in the innovation policy of all developed market economies. The economic literature distinguishes various typologies of innovation systems. The aim of the article is to assess the effectiveness of the system of European integration, the socio-democratic system, and the mutated system, measured by the level of innovation of the economies that belong to these systems, in 2014 and 2019. The article analyzes the literature on the subject of innovation systems. The method of linear ordering, which makes it possible to build a synthetic measure calculated using the Hellwig method, is used to assess the effectiveness of innovation systems. The article formulates a research hypothesis that the most effective innovation systems are the socio-democratic system and the system of European integration. This hypothesis has been positively verified.
Keywords: O30; O31; O43; 330; innovation; national innovation system; innovation ranking